Apolipoprotein E epsilon 4 genotype and a physically active lifestyle in late life: analysis of gene–environment interaction for the risk of dementia and Alzheimer's disease dementia. Issue 6 (April 2014) - Luck, T.; Riedel-Heller, S. G.; Luppa, M.; Wiese, B.; Köhler, M.; Jessen, F.; Bickel, H.; Weyerer, S.; Pentzek, M.; König, H.-H.; Prokein, J.; Ernst, A.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background As physical activity may modify the effect of the apolipoprotein E (APOE) ε4 allele on the risk of dementia and Alzheimer's disease (AD) dementia, we tested for such a gene–environment interaction in a sample of general practice patients aged ⩾75 years. Method Data were derived from follow-up waves I–IV of the longitudinal German study on Ageing, Cognition and Dementia in Primary Care Patients (AgeCoDe). The Kaplan–Meier survival method was used to estimate dementia- and AD-free survival times. Multivariable Cox regression was used to assess individual associations of APOE ε4 and physical activity with risk for dementia and AD, controlling for covariates. We tested for gene–environment interaction by calculating three indices of additive interaction. Results Among the randomly selected sample of 6619 patients, 3327 (50.3%) individuals participated in the study at baseline and 2810 (42.5%) at follow-up I. Of the 2492 patients without dementia included at follow-up I, 278 developed dementia (184 AD) over the subsequent follow-up interval of 4.5 years. The presence of the APOE ε4 allele significantly increased and higher physical activity significantly decreased risk for dementia and AD. The co-presence of APOE ε4 with low physical activity was associated with higher risk for dementia and AD and shorter dementia- and AD-free survival time than the presence of APOE ε4 or low physical activity alone. Indices of interaction indicated no significant interaction between low physical activity and the APOE ε4 allele for general dementia risk, but a possible additive interaction for AD risk. Conclusions Physical activity even in late life may be effective in reducing conversion to dementia and AD or in delaying the onset of clinical manifestations. APOE ε4 carriers may particularly benefit from increasing physical activity with regard to their risk for AD.